Village Fund Management in Indonesia: Impact on Government Performance in Madiun - Lasboi, Yorim N; Sumtaky, Maxion; Assih, Prihat (Journal of Regional Economics Indonesia, 2024)
This study examines the strategic impact of village fund management on the performance of village governments in Madiun Regency, Indonesia. Using a sample of 27 villages and 80 respondents, including village heads, secretaries, and financial officers, the research investigates how planning, implementation, transparency, and accountability affect governmental performance. Data were collected through documentation and questionnaires and analyzed using multiple linear regression. The results show that both planning and accountability have a positive and significant influence on village government performance, while implementation also contributes positively. However, transparency does not significantly impact performance. The findings suggest that improving planning and accountability processes is essential for enhancing the effectiveness of village governance. In contrast, transparency efforts, while important, may not directly lead to performance improvements in this context. The study highlights the need for better public access to information and more active participation in performance evaluations to further enhance village fund management and its outcomes.